Reaction Pathways Involved in CH4 Conversion on Pd/Al2O3 Catalysts: TAP as a Powerful Tool for the Elucidation of the Effective Role of the Metal/Support Interface - Renème, Y.; Pietrzyk, S.; Dhainaut, F.; Chaar, M.; van Veen, A. C.; Granger, Pascal (Frontiers in Chemistry, 2016)
Temporal Analysis of Products (TAP) reactor offers an alternative to draw direct structure/activity relationships checked on Natural Gas-fuelled Vehicle (NGV) catalysts Determination of accurate kinetic constants for methane adsorption from single pulse experiments and subsequent investigation of sequential surface reactions from alternative CH4/O2 pulse experiments provides a straightforward visualization of the involvement of the metal/support interface on freshly-prepared catalysts and the loss of this effect on aged single palladium based catalysts.